An Early Upper Palaeolithic decorated bone tubular rod from Pod Hradem Cave, Czech Republic. (March 2014) - Wright, Duncan; Nejman, Ladislav; d'Errico, Francesco; Králík, Miroslav; Wood, Rachel; Ivanov, Martin; Hladilová, Šárka
Abstract : Personal ornaments are a notable feature of the Early Upper Palaeolithic in Europe and an important expression of modern human identity. The tubular bone rod from Pod Hradem Cave in the Czech Republic is the first example of its kind from Central Europe. Laboratory examination reveals the techniques used in its manufacture and underlines the skill of its maker. AMS dates and Bayesian modelling suggest a cultural association with the Early Aurignacian period. It illustrates the cultural links across large areas of Europe at this time, although it is unique in its specific combination of size, raw material and decorative features.